Aumento de semillas de phaseolus albicarminus (Leguminosae, Phaseoleae) mediante técnicas de propagación asexual - Sabogal Carvajal, Ramiro Andres (2024)
Phaseolus albicarminus, wild relative of the cultivated bean; It is endemic to Costa Rica and is in danger of extinction. The Future Seeds germplasm bank (Palmira - Colombia) safeguards a single accession (G40901) of this wild bean. The availability of original seeds, the production of new seeds of P. albicarminus is limited and scarce. It is susceptible to attack by nematodes and root rot, this creates a risk for the accession. This research evaluated asexual propagation, to identify appropriate conditions to produce enough seeds of this species. Two experiments were carried out under controlled conditions: i. Propagation by layering cuttings and grafts was compared to increase the number of plants and seeds of P. albicarminus; ii. The compatibility of 16 bean accessions as rootstocks to propagate P. albicarminus was evaluated. The results of the first experiment indicate that grafts (75% budding) are significantly more effective in propagating P. albicarminus, compared to layering (25% budding) and cuttings (16.6% budding). In the second experiment, three rootstocks (1 P. coccineus, 1 P. dumosus, 1 P. vulgaris) were identified for the successful propagation of P. albicarminus. The use of these rootstocks counteracts the susceptibility of P. albicarminus to soil problems (fungi and nematodes), and it was also possible to shorten the days of flowering. Using grafts, 53 P. albicarminus plants were established distributed in different experimental stations and to date 7 seeds have been produced. This method has also allowed the production of 673 seeds of P. chiapasanus (G40790) and 234 seeds of a hybrid of P. vulgaris x P. dumosus (G36387); demonstrating that it is an alternative for regeneration in germplasm banks.